Effectiveness of Health Services at the Community Health Center: Efektivitas Pelayanan Kesehatan Di Pusat Kesehatan Masyarakat - Hidayati, Nuril; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2022)
The effectiveness of health services is carried out to increase the satisfaction of the people who seek treatment. Problems with services are timeliness, community dissatisfaction, and indiscipline of health workers in providing services. This research method uses descriptive qualitative through interviews, observation and documentation. Determination of informants by purposive sampling involved, namely the head, coordinator, administrator, dental practitioner, MCH/KB implementer, drug and pharmacy implementer through data collection, data reduction, data presentation, and drawing conclusions. The results of the study are the effectiveness of services by improving facilities and infrastructure, and the quality of human resources. It is proven by the implementation of the nutrition post program for weighing and measuring the height of toddlers so that parents are trained to choose food for their child's growth and development, the free covid-19 vaccination program. The supporting factor is the collaboration between health workers, village government, and the community and periodic evaluation by analyzing the results of the suggestion box. The inhibiting factor is timeliness and indiscipline, causing public dissatisfaction with services. Keyword: , , .